Lipids production from Scenedesmus obliquus through carbon/nitrogen ratio optimization (2019)
Microalgae are one of the most promising sources of raw material for biofuel production and derivatives since its high yield of biomass and metabolites possess a low environmental impact. However, its implementation on large scale facilites still faces challenges such as the optimisation of lipid production (due to strain capacity and environmental factors) and downstream processes (extraction and separation of the lipidic fraction). The objective of the present investigation was to determine the potential of the carbon/nitrogen ratio as a technical tool for the improvement of total lipids on Scenedesmus obliquus. The carbon/nitrogen ratio was evaluated using a non-factorial design coupled with surface response methodology with sodium bicarbonate and sodium nitrate as carbon and nitrogen source. Results showed that the optimal conditions that enhanced the lipid deposition (up to 66% w/w) were 1.5 g L-1 sodium bicarbonate and 0,125 g L-1 of sodium nitrate. Finally, the results of the fatty acid profile shown the presence of stearic acid (C18: 0) with 22.63% and elaidic acid (C18:1) with 77.38%, with the absence of fatty acids of two or more double bonds. In conclusion, the adjustment in the carbon/nitrogen ratio favours the final deposition of lipids in Scenedesmus obliquus which is emerging as a possible candidate for the production of lipids of interest for the generation of biodiesel.